Komunikasi Dakwah Guru Mengaji Dalam Pembinaan Akhlak Santri TPQ Ulumul Qur’an An-Nur Kelurahan Mampu Kecamatan Wajo Kota Makassar - Rahman, Fahmi; Hakim, Ahmad; Abdullah, Nuraeni (Universitas Muslim Indonesia, 2021)
Based on this observation, in order to know the communication of da'wah by the Koran teacher and to know the moral development of the students of TPQ Ulumul Qur'an An-Nur, Mampu sub-district, Wajo sub-district, Makassar city. This research uses descriptive qualitative research. Data collection techniques using the method of observation, interviews and documentation. Data analysis techniques used are drawing conclusions, data reduction and data presentation. The results of this study are TPQ Ulumul Qur'an An-Nur with iqro' learning, memorizing prayers, storytelling methods or inspirational stories, ta'widiyah (habituation) methods, methods of playing and learning and singing. With this applied method, students can more easily understand and practice what is received from the Koran teacher so that they can form commendable morals to students.